Comparação da capacidade funcional entre diabéticos tipo 2 com diferentes níveis de prática de atividade física - Silva, Leonan Amaral da (Brasil, 2025)
INTRODUCTION: Diabetes mellitus (DM) is a chronic and heterogeneous metabolic disorder characterized by elevated blood glucose levels, with type 2 DM accounting for about 95% of all diabetes cases. Regular physical activity provides substantial benefits for individuals with diabetes; thus, functional capacity is an important predictor of survival for various cardiovascular and non-cardiovascular diseases. However, the comparison of the impact of physical activity levels on functional capacity in adults with type 2 diabetes is still poorly explored. OBJECTIVE: To compare the functional capacity among individuals with type 2 diabetes with different levels of physical activity. METHODS: This is a cross-sectional analytical study conducted between August 2023 and July 2024 at the Institute of Health and Biotechnology of the Federal University of Amazonas, located in Coari/AM. The sample consisted of individuals diagnosed with type 2 DM aged over 18 years. All participants signed the Informed Consent Form. We assessed functional capacity and physical activity level using the Glittre-ADL test and the IPAQ-SF, respectively. RESULTS: When comparing physically active subjects to sedentary ones, a significant difference was observed (pbonf= 0.047), with physically active individuals showing an average time 77.2 seconds lower. CONCLUSION: The study revealed that participants with type 2 diabetes who regularly engaged in physical activities exhibited superior functional capacity compared to sedentary individuals.